2014
DOI: 10.1016/j.nut.2014.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Artemisia species on de novo lipogenesis in vivo

Abstract: Objective Botanical compounds and extracts are widely used as nutritional supplements for the promotion of health or prevention of disease. An extract of Artemisia dracunculus (PMI 5011) has been shown to improve insulin action, yet the precise mechanism is not known. We proposed that the mechanism by which PMI 5011 and two related Artimisia extracts improve insulin action is associated with a downregulation of DNL in the liver and an increase in DNL in the adipose tissue. Materials/Methods DIO old male mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The sample was then derivatized using 100 l of pyridine: acetic anhydride (1:2). Samples were heated at 60°C for 30 min, dried under nitrogen, and then resuspended in ethyl acetate for analysis by GC-MS (Agilent, Santa Clara, CA) (52).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample was then derivatized using 100 l of pyridine: acetic anhydride (1:2). Samples were heated at 60°C for 30 min, dried under nitrogen, and then resuspended in ethyl acetate for analysis by GC-MS (Agilent, Santa Clara, CA) (52).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies revealed that SCO is a highly specific activator of peroxisome proliferator-activated receptor-␥ (PPAR␥) but not of any other nuclear receptor (47). In vivo, SCO, administered by oral gavage or through diet supplementation, exerts metabolically beneficial effects such as improved whole body insulin sensitivity and reduced circulating triglycerides and adiponectin, as well as many favorable effects on adipose tissue, including enhanced endocrine function and insulin signaling, and reduced monocyte chemoattractant protein-1 (MCP-1) levels, while producing no changes in body weight, food intake, body composition (47,49,65), fat pad weight independent of depot (observed, data not published), or de novo lipogenesis in liver or adipose tissue (52). In vitro, experiments in 3T3-L1 cells have also demonstrated SCO's ability to enhance adipogenic differentiation and to reduce tumor necrosis factor-␣ (TNF␣)induced changes in inflammatory gene expression and adipokine secretion (49).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance is induced by the accumulation of lipid metabolites from excess fat in insulin sensitive cells. Excess dietary carbohydrate not stored as glycogen or oxidized for energy is converted to fat by de novo lipogenesis 4 . Among the fatty acid derived metabolites, ceramides are most active in negatively regulating insulin signaling 5 6 .…”
mentioning
confidence: 99%
“…However, in a mouse model of diet-induced obesity (DIO) and insulin resistance, SCOPA administration by gavage or supplementation of diet was found to improve insulin sensitivity as measured by homeostatic model assessment for insulin resistance (HOMA-IR) or insulin tolerance test (ITT) (48)(49)(50). Circulating levels of triglycerides, free fatty acids (FFAs), glycerol, and insulin (fasting) were reduced, while adiponectin levels were increased (49)(50)(51). In liver, SCOPA supplementation reduced hepatic triglyceride and cholesterol content and enhanced insulin-induced phosphorylation of the signaling proteins insulin receptor substrate (IRS-1), insulin receptor subunit beta (IRb), protein kinase B (AKT1), and RAC-beta serine/threonine protein kinase (AKT2) (50).…”
Section: Effects Of a Scoparia On Determinants Of Metabolic Health Me...mentioning
confidence: 99%